A case study of mechanical and metallurgical properties of friction stir welded AA6063 AMC. (2018) - Kaushik, Narinder; Singhal, Sandeep
This experimental work deals with the comparative examination of microstructural and mechanical properties of as cast and friction stir welded, AA6063/SiC matrix composite. AA6063/10.5 wt. % SiC aluminium matrix composite was produced by employing stir casting route. Specimen Plates having thickness 6mm were cut from the fabricated composite matrix and friction stir welded successfully. The friction stir welding (FSW) was performed by using a tool rotational rate of 1400 rpm and tool transverse rate of 124 mm/min. A square pin profiled tool made of AISI H13 tool steel was used. The microstructural study revealed that FSW produced a notable reduction in the size of reinforcement agents and their homogeneous distribution in the stir zone as compared to the base metal composite matrix. Frictional heat generated during FSW had impacts on the growth, dissolution and reprecipitation of the hardening precipitates. The microstructural changes resulted in improved mechanical properties. The scanning electron microscopic (SEM) fracture analysis revealed that the fracture behaviour was changed from ductile to brittle after FSW.